2015
DOI: 10.1038/bjc.2014.638
|View full text |Cite
|
Sign up to set email alerts
|

mTOR inhibition improves fibroblast growth factor receptor targeting in hepatocellular carcinoma

Abstract: Background:Systemic therapy has proven only marginal effects in hepatocellular carcinoma (HCC) so far. The aim of this study was to evaluate the effect of targeting fibroblast growth factor receptor (FGFR) on tumour and stromal cells in HCC models.Methods:Human and murine HCC cells, endothelial cells (ECs), vascular smooth muscle cells (VSMCs), hepatic stellate cells (HSCs), human HCC samples, FGFR inhibitor BGJ398 and mammalian target of rapamycin (mTOR) inhibitor rapamycin were used. Effects on growth, motil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 35 publications
1
31
0
Order By: Relevance
“…However, these TKIs are not selective for FGFR3 (Mohammadi et al, 1997; Dimitroff et al, 1999). Recently, NVP-BGJ398, a TKI more selective for FGFR3 over others FGFRs (Gudernova et al, 2016) was used in preclinical murine models for treating several FGFR-related cancers such as malignant rhabdoid tumors (Wohrle et al, 2013b), hepatocellular carcinoma (Scheller et al, 2015) and skeletal disorders including FGF23-mediated hypophosphatemic rickets (Wohrle et al, 2013a) and Ach (Komla-Ebri et al, 2016). Importantly, NVP-BGJ398 was shown in vivo to reduce FGFR3(p.Tyr367Cys) activation and improve the skeletal phenotype of Ach-like mice (Komla-Ebri et al, 2016).…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…However, these TKIs are not selective for FGFR3 (Mohammadi et al, 1997; Dimitroff et al, 1999). Recently, NVP-BGJ398, a TKI more selective for FGFR3 over others FGFRs (Gudernova et al, 2016) was used in preclinical murine models for treating several FGFR-related cancers such as malignant rhabdoid tumors (Wohrle et al, 2013b), hepatocellular carcinoma (Scheller et al, 2015) and skeletal disorders including FGF23-mediated hypophosphatemic rickets (Wohrle et al, 2013a) and Ach (Komla-Ebri et al, 2016). Importantly, NVP-BGJ398 was shown in vivo to reduce FGFR3(p.Tyr367Cys) activation and improve the skeletal phenotype of Ach-like mice (Komla-Ebri et al, 2016).…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…Schmidt et al (2016) revealed that the classification system may help identify HCC patients who are most likely to benefit FGFR inhibition. Furthermore, combined FGFR/mTOR treatment showed significant inhibitory effects on signaling and motility in HCC (Scheller et al, 2015). Inhibition of the PI3K/AKT/mTOR pathway was also shown to be beneficial for suppression of angiogenesis in HCC (Jung et al, 2012), and provided insight into promising strategies for targeted therapies (Fang et al, 2012).…”
Section: Discussionmentioning
confidence: 97%
“…49 In addition, Scheller et al have also shown that a small panel of S2 cell lines are responsive to BGJ398 and that this effect could be enhanced with the addition of an mTOR inhibitor. 50 Finally, while non-S2 phenotypes were associated with resistance to therapy in most preclinical investigations above, a non-AFP-secreting "progenitor-like" molecular subtype of HCC was recently reported to be sensitive to the Src/Abl inhibitor dasatinib. 13,51 There is significant evidence that FGFR4 overexpression is common enough in human HCC to make this strategy worthy of clinical trials for HCC.…”
Section: Discussionmentioning
confidence: 99%
“…The absorbance at 562 nm was measured with a spectrophotometric plate reader (Emax, Molecular Devices, Sunnyvale, CA) and the experiment was repeated twice for each cell line. IC 50 value was defined as the drug concentration yielding 50% nonsurviving cells compared with vehicle-treated controls.…”
Section: Cell Growth Assaymentioning
confidence: 99%